Site‐specific Bioconjugation and Convergent Click Chemistry Enhances Antibody–Chromophore Conjugate Binding Efficiency. (15th April 2020) - Sadiki, Amissi; Kercher, Eric M.; Lu, Haibin; Lang, Ryan T.; Spring, Bryan Q.; Zhou, Zhaohui Sunny
Abstract: Photosensitizer (PS)–antibody conjugates (photoimmunoconjugates, PICs) enable cancer cell‐targeted photodynamic therapy (PDT). Nonspecific chemical bioconjugation is widely used to synthesize PICs but gives rise to several shortcomings. The conjugates are heterogeneous, and the process is not easily reproducible. Moreover, modifications at or near the binding sites alter both binding affinity and specificity. To overcome these limitations, we introduce convergent assembly of PICs via a chemo‐enzymatic site‐specific approach. First, an antibody is conjugated to a clickable handle via site‐specific modification of glutamine (Gln) residues catalyzed by transglutaminase (TGase, EC 2.3.2.13). Second, the modified antibody intermediate is conjugated to a compatible chromophore via click chemistry. Utilizing cetuximab, we compared this site‐specific conjugation protocol to the nonspecific chemical acylation of amines using N‐hydroxysuccinimide (NHS) chemistry. Both the heavy and light chains were modified via the chemical route, whereas, only a glutamine 295 in the heavy chain was modified via chemo‐enzymatic conjugation. Furthermore, a 2.3‐fold increase in the number of bound antibodies per cell was observed for the site‐specific compared with nonspecific method, suggesting that multiple stochastic sites of modification perturb the antibody–antigen binding. Altogether, site‐specific bioconjugation leads to homogenous, reproducible and well‐defined PICs, conferring higher binding efficiency and probability of clinical success. Abstract : Photosensitizer–antibody conjugates (PACs or PICs) enable targeted photodynamic therapy. Widely used nonspecific chemical bioconjugation methods for PIC synthesis are limited by their heterogeneity, irreproducibility and crucially, their adverse effect on antibody structure, binding affinity and specificity. Alternatively, we employ a site‐specific, enzymatic conjugation strategy which yields homogenous, reproducible and well‐characterized PICs with a higher binding efficiency compared to their nonspecific counterpart. The process is broadly applicable to a number of antibodies and chromophores ( e.g. photosensitizers or fluorophores), thereby enabling rapid generation of diverse libraries of PICs with tailored functionality that retain the native biological activity of the antibody.